ANALISIS PERANCANGAN FITUR PADA SISTEM ERP UNTUK INVENTORY MODULE DI PT XYZ UNTUK MENGURANGI BULLWHIP EFFECT - Hery Hery; Jansen Wiratama; Wiracayana Ratanaghara Jayamangala (Jurnal Ilmiah Matrik, 2022)
PT XYZ, which is implementing ERP for the POS and Inventory modules, made a request to modify the ERP system, especially the inventory module to reduce the Bullwhip Effect (BE), where when this system was implemented it did not yet have this feature, but PT XYZ's request needed to be analyzed further. so that the developed features do not waste resources, budget and time from the project. To validate the request for modification of PT XYZ, it is necessary to analyze the identification of non-conformities first by conducting in-depth interviews with the top management of PT XYZ who were selected based on purposive sampling with the criteria of 1 decade of work and the party responsible for supervising all divisions at PT XYZ , the top management statement is supported by the calculation of the value of the bullwhip effect and data visualization. After it was proven that there was a bullwhip effect at PT XYZ and supported by the results of the BE calculation for 5 outlets, all of which exceeded the BE parameter, and found the cause of BE through data visualization in which PT XYZ forecast demand. Based on the data and facts that have been collected, prototype features are designed that can reduce BE as stated in the Product Requirement Document where product requests, delivery and receipts are included in the prototype features and the type of prototype used is an evolutionary prototype. The prototype was tested for 1 month and according to the Management Representative's and BE calculation results after the implementation of the feature showed a reduction in the Bullwhip effect on PT XYZ Keywords : Bullwhip Effec, ERP Modification, Product Requirement Document, Prototype, Supply Chain